Monitoring the sensitivity of influenza viruses to oseltamivir, in Romania, from 2016 to 2023 - Mihai Maria Elena; Ivanciuc Alina Elena; Cherciu Carmen Maria; Mihăescu Grigore; Lazăr Mihaela (Romanian Journal of Laboratory Medicine, 2024)
Introduction: influenza is an acute viral disease caused by infection of the upper respiratory tract - difficult to control, which affects a large part of the population. Neuraminidase inhibitors (NAIs), such as oseltamivir and zanamivir, are the antiviral drugs utilized in Romania for the treatment of respiratory infections caused by the influenza viruses. The objective of the study is to monitor and analyze influenza viruses circulating in Romania, in terms of their susceptibility to oseltamivir, with the aim of signalling the emergence of viral strains resistant to antivirals.